1980
DOI: 10.2118/8401-pa
|View full text |Cite
|
Sign up to set email alerts
|

Improved Ball Sealer Diversion

Abstract: Laboratory and field studies are described which demonstrate that diversion of well stimulation treatments can be improved dramatically by using buoyant ball sealers. These sealers have extended ball sealer applicability to treatments conducted at low perforation flow rates. The development of an improved ball sealer has resulted in the implementation of several successful field treatments. Introduction One major obstacle often limiting the success of well st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 1 publication
1
16
0
1
Order By: Relevance
“…The success of a ball sealer treatment depends critically on a number of parameters: ball density ("floaters" or "sinkers"), fluid viscosity, pump rate, and number of open perforations. 9 The complexity of the process makes it difficult to optimize a treatment without the use of a simulator.…”
Section: Ball Sealer Diversionmentioning
confidence: 99%
“…The success of a ball sealer treatment depends critically on a number of parameters: ball density ("floaters" or "sinkers"), fluid viscosity, pump rate, and number of open perforations. 9 The complexity of the process makes it difficult to optimize a treatment without the use of a simulator.…”
Section: Ball Sealer Diversionmentioning
confidence: 99%
“…Успешность обработки с использованием уплотнительных шаров зависит от нескольких параметров: плотности шаров (плавающие или тонущие шары), вязкости жидкости, скорости подачи насоса и количества открытых перфорационных отверстий. 9 Сложность процесса затрудняет оптимизацию обработки без моделирования.…”
Section: отклонение твердыми частицамиunclassified
“…However, those nonbuoyant ball sealers often fail to provide a satisfactory diversion effect (Stipp 1968;Webster et al 1965) because of low injection rate and high perforation density (Bale 1984). Erbstoesser (1980) conducted laboratory tests with ball sealers having various densities, and found that buoyant ball sealers provided higher seating efficiencies (the ratios of the total number of balls seated to the number of balls injected) when compared to nonbuoyant ball sealers, especially at low flow rates. From the tests, he also identified three other parameters of critical importance to ball-sealer seating efficiency: flow rate through the perforations, flow rate past the perforations, and fluid viscosity.…”
Section: Introductionmentioning
confidence: 99%